Strategic Alliances and Associativism Networks as a Source of Competitiveness Advantage in the Retailers Market of Construction - Manãs, Antonio Vico; Pacanhan, Mário Ney (Review of Business Management, 2007)
The analysis of organizational processes leads to the need of strategic positioning and constant search for competitive advantage. The main topic of this paper is strategic alliances. Many academics have suggested that this concept may provide both differentiation and cooperation, especially for small companies. The present paper examines the truth of this claim, especially in the case of associative networks. The experience of 181 small retailers in the construction supply business provides the data to broach the concepts of the strategic alliance model, and to analyses its advantages and disadvantages. The study allows us to look deeper into the process of organizational formation and reformation and into the positive and negative aspects which occur in this intern process and in the competition and competence relations with the market. Key-words: Alliances. Network. Associativism. Cooperation. Process.